Assessment of the physical condition of the high-level wheelchair tennis player according to competitive level and kind of injury - Sánchez-Pay, A.; Sanz-Rivas, D. (Revista Internacional de Ciencias del Deporte, 2019)
Testing the physical condition of athletes allows to know which aspects should be improved on the player, as well as the level of physical condition of the player with respect to normative groups, among others. The aim of this study was to test the fitness levels of wheelchair tennis (WT) players and establish comparisons based on their ranking and their level of impairment. The participants in this research were 9 male high-level WT players. The players completed a battery of tests consisting in the following tests: forearm strength, speed of service, sprint in 5, 10, and 20 m (with and without racket), agility test (with and without racket), medicine ball throw test (serve, forehand, and backhand movements) and an endurance specific wheelchair tennis test. The results showed that the highest-level players have better fitness levels in all the tests, finding significant differences in almost all of them. The players with greater functional limitation showed lower values, although a large number of statistically significant differences were not found. This test battery used can be used to assess the fitness levels of WT players because they discriminate depending on the level of the athlete, and are not exclusive in relation to their activity limitation.